2009
DOI: 10.1124/jpet.108.143362
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Melanin-Concentrating Hormone Receptor 1 Antagonism for the Treatment of Obesity and Depression

Abstract: The mammalian neuropeptide, melanin-concentrating hormone, interacts with two G protein-coupled receptors, melanin-concentrating hormone receptor (MCHR) 1 and MCHR2; however, only MCHR1 is expressed in rats and mice. In the present study, we evaluated MCHR1 antagonism in preclinical models believed to be predictive of antiobesity and antidepressant activity. Central activity of the selective MCHR1 antagonist, GW803430 [6-(4-chloro-phenyl)-3-[3-methoxy-4-(2-pyrrolidin-1-yl-ethoxy)-phenyl]-3H-thieno[3,2-d]pyrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 44 publications
3
67
0
Order By: Relevance
“…Anyway, our finding about MCH/Fos reducing the effect of escitalopram raises several intriguing new questions regarding the clinical effects of escitalopram and other SSRI antidepressants. One of these could be that the effect of serotonin on MCHcontaining neurons (van den Pol et al 2004) may be a pivotal component in the antidepressant effect of SSRIs, regarding that selective MCH1-R antagonist agents show antidepressant-like effects (Borowsky et al 2002;Gehlert et al 2009) and MCH administered into the dorsal raphe evokes a depressive-like behavior (Lagos et al 2011b;Torterolo et al 2011). In contrast, the role of REM reduction may be questioned by the fact that there are other effective antidepressants, such as bupropion, with its main effect on the noradrenergic and dopaminergic system without affecting the serotonergic system and not suppressing REMS either in human controls or depressed patients (Wilson and Argyropoulos 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, our finding about MCH/Fos reducing the effect of escitalopram raises several intriguing new questions regarding the clinical effects of escitalopram and other SSRI antidepressants. One of these could be that the effect of serotonin on MCHcontaining neurons (van den Pol et al 2004) may be a pivotal component in the antidepressant effect of SSRIs, regarding that selective MCH1-R antagonist agents show antidepressant-like effects (Borowsky et al 2002;Gehlert et al 2009) and MCH administered into the dorsal raphe evokes a depressive-like behavior (Lagos et al 2011b;Torterolo et al 2011). In contrast, the role of REM reduction may be questioned by the fact that there are other effective antidepressants, such as bupropion, with its main effect on the noradrenergic and dopaminergic system without affecting the serotonergic system and not suppressing REMS either in human controls or depressed patients (Wilson and Argyropoulos 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown GW803040 inhibited MCHR1 binding in different areas of the brain and exhibits substantial occupancy of the MCHR1 at doses of 1 mg kg À1 or greater (23). These authors (23) further evaluated the effects of the same compound at a dose of 10 mg kg À1 in MCHR1 þ/þ and MCHR1 À/À mice, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown GW803040 inhibited MCHR1 binding in different areas of the brain and exhibits substantial occupancy of the MCHR1 at doses of 1 mg kg À1 or greater (23). These authors (23) further evaluated the effects of the same compound at a dose of 10 mg kg À1 in MCHR1 þ/þ and MCHR1 À/À mice, respectively. The fact that MCHR1 À/À mice did not show a decrease in body weight, but MCHR1 þ/þ mice did, suggested that GW803040 produced significant reductions in body mass, fatness and food intake via MCHR1 antagonism (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations